Agricultural Drought Assessment using Remote Sensing Data (Case study: Tuyserkan County) - Maedeh Malmir; Kamran Shayesteh; Iman Pazhouhan (بوم شناسی کشاورزی)
Introduction In recent years, with the growing significance of drought and climate change, there is an increasing need for a well-structured plan to implement effective management strategies and monitor drought conditions. Considering the importance of investigating agricultural drought in relation to the yield of agricultural products and the fact that agriculture in Iran has always been affected by the amount and distribution of inappropriate rainfall, and climate change has caused problems in the cultivation conditions in the country by causing anomalies in temperature and precipitation; in recent years, due to the lack of suitable moisture conditions in the soil and the decrease of rainfall in the spring season, the amount of production and the quality of products have suffered serious threats, among these threats is the threat to human food security and, by nature, social and economic problems. Effective monitoring at the right moment can greatly reduce damage to agricultural production. The use of remote sensing and satellite imagery as effective tools for monitoring agricultural drought has gained significant attention from researchers. Remote sensing allows for the study of drought's effects on plant growth, leading to more accurate and impactful results in drought modeling. Materials and Methods Tuyserkan city covers an area of 1,556 square kilometers, 7.98% of the area of Hamedan province, in the west of Iran, and it is located along the Zagros mountain range. In this study, the goal is to evaluate the spatial and temporal patterns of agricultural drought in Tuyserkan County using vegetation coverage indicators derived from satellite data, including the Normalized Difference Vegetation Index (NDVI), the Vegetation Condition Index (VCI), the Plant Health Index (VHI), and the Thermal Condition Index (TCI), over a 20-year period and at seasonal and annual scales. The satellite data used in this study are from MODIS imagery. These images are a suitable tool for drought monitoring due to the power of proper spatial separation and providing bands with different wavelengths. After pre-processing these images using ENVI software, surface temperature, and rainfall data (used by interpolation method) are used as effective data in the drought process in the study area during this period. Results and Discussion The Vegetation Condition Index (VCI) has a significant correlation with different seasons, as well as with the Standardized Precipitation Index (SPI). Therefore, it can be stated with confidence that this index can be used to monitor temporal and spatial changes in agricultural droughts in the study area with acceptable accuracy. In fact, the months from the fourth to the sixth are the best time for the growth and development of plants because whatever the effect of precipitation, it will show itself during this period, and the highest correlation between the SPI and VCI for the fourth to the sixth months. However, in the VHI for the seventh to ninth months, the meaningful correlation could be because of the fact that the vegetation of Tuyserkan is mostly farmland (ending in October) and orchard (with a high amount of walnuts and almonds, which continue until September). Rahimzadeh et al. (2008) found the best correlation between the VCI and SPI for one to three months in the monitoring of droughts in Northwest Iran, and in this study, the correlation between the VCI and SPI for one to nine months was obtained. Generally, the VCI index provides better results for measuring precipitation, especially in areas that are climatically heterogeneous. As a result, the VCI was selected as the best index for monitoring agricultural droughts in the region. ConclusionBased on the calculations performed, the climate of the region matches the seasonality of the Vegetation Coverage Index (VCI) better. Generally, the results of the VCI and SPI indices largely confirm the results of the NDVI index. As a result, the VCI index was chosen as the best index for monitoring agricultural droughts in Tuyserkan County. Additionally, the results derived from the use of the vegetation index VCI indicate the state of droughts in 2008 and 2014 and the state of precipitation in 2007 and 2018 compared to the study period in the region.